The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1038/s41467-022-35642-2
|View full text |Cite
|
Sign up to set email alerts
|

Broadly neutralizing and protective nanobodies against SARS-CoV-2 Omicron subvariants BA.1, BA.2, and BA.4/5 and diverse sarbecoviruses

Abstract: As SARS-CoV-2 Omicron and other variants of concern (VOCs) continue spreading worldwide, development of antibodies and vaccines to confer broad and protective activity is a global priority. Here, we report on the identification of a special group of nanobodies from immunized alpaca with potency against diverse VOCs including Omicron subvariants BA.1, BA.2 and BA.4/5, SARS-CoV-1, and major sarbecoviruses. Crystal structure analysis of one representative nanobody, 3-2A2-4, discovers a highly conserved epitope lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 91 publications
2
24
0
Order By: Relevance
“…We obtained different groups of Nbs that exhibited high sequence variability and were originated from a diverse set of V, D, and J genes (Fig 1). Our results are consistent with those obtained by other groups screening camelid-derived libraries, where an impressive diversity in the Nb nucleotide sequence, specificity and neutralizing capacity was found, especially after successive immunizations to promote the development of superimmunity [48,49]. This is particularly relevant considering the emergence of new VOCs, since the screening of a large library, like the one we described in this work, constructed from hyperimmunized animals, can broaden the type of Nbs obtained and increase the probability of finding binders that recognize new variants.…”
Section: Discussionsupporting
confidence: 92%
“…We obtained different groups of Nbs that exhibited high sequence variability and were originated from a diverse set of V, D, and J genes (Fig 1). Our results are consistent with those obtained by other groups screening camelid-derived libraries, where an impressive diversity in the Nb nucleotide sequence, specificity and neutralizing capacity was found, especially after successive immunizations to promote the development of superimmunity [48,49]. This is particularly relevant considering the emergence of new VOCs, since the screening of a large library, like the one we described in this work, constructed from hyperimmunized animals, can broaden the type of Nbs obtained and increase the probability of finding binders that recognize new variants.…”
Section: Discussionsupporting
confidence: 92%
“…Importantly, both C-282 and C-39 showed superior affinities when binding to multiple SARS-CoV-2 variants compared to previously reported nanobodies (Figure ). , Furthermore, a comparison with results from pseudovirus experiments revealed that these nanobodies exhibit high neutralizing activity against multiple mutant variants, with IC 50 values comparable to those of previously reported nanobodies (Supporting Information Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…In 2022, researchers identified and prepared 124 purified nanobodies exhibiting neutralizing activity against the prototype SARS-CoV-2 pseudovirus. However, only three nanobodies demonstrated broad neutralizing activity against WT, Alpha, Delta, and Omicron variants . These findings underscore the limitations of relying exclusively on traditional ELISA, or pseudovirus, and live virus-based assays, as they can identify only one variant at a time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, researchers reported the isolation and characterization of a novel group of nanobodies from immunized alpacas [ 57 ]. These nanobodies, exemplified by the protein 3-2A2-4, have potency against Omicron subvariants BA.1, BA.2, BA.2.12.1, and BA.4/5, SARS-CoV-1, and key representative coronaviruses from bats and pangolins.…”
Section: Nanotechnology Solutions To the Challenge Of Sars-cov-2mentioning
confidence: 99%